Small size today, aquarium dumping tomorrow: sales of juvenile non-native large fish as an important threat in Brazil - Magalhaes, Andre L. B. (2017)
Informal sales of large-bodied non-native aquarium fishes (known as tankbusters) is increasing among Brazilian hobbyists. In this study, we surveyed this non-regulated trade on Facebook (R) from May 2012 to September 2016, systematically collecting information about the fishes available for trading: species, family, common/scientific names, native range, juvenile length, behavior, number of specimens available in five geographical regions from Brazil. We also assessed the invasion risk of the most frequently sold species using the Fish Invasiveness Screening Test (FIST). We found 93 taxa belonging to 35 families. Cichlidae was the dominant family, and most species were native to South America. All species are sold at very small sizes (< 10.0 cm), and most display aggressive behavior. The hybrid Amphilophus trimaculatus x Amphilophus citrinellus, Astronotus ocellatus, Uaru amphiacanthoides, Osteoglossum bicirrhosum, Cichla piquiti, Pangasianodon hypophthalmus, Datnioides microlepis and Cichla kelberi were the main species available. The southeast region showed the greatest trading activity. Based on biological traits, the FIST indicated that Arapaima gigas, C. kelberi and C. temensis are high-risk species in terms of biological invasions via aquarium dumping. We suggest management strategies such as trade regulations, monitoring, euthanasia and educational programs to prevent further introductions via aquarium dumping.